Thin Film Silicon Solar Cell Prepared By Thermal Evaporation On Polyimide Substrate - Pakhuruddin, Mohd Zamir (2012)
Conventional wafer-based silicon (Si) technology still dominates around 90% of the photovoltaic (PV) market with 15 - 20% conversion efficiency due to its abundance (~25% of silica in the earth’s crust), non-toxicity besides having close to ideal band gap (1.12 eV) for photoconversion process. But, this technology suffers from high cost/Wattp (USD 2 - 3/Wattp at present) that impedes its widespread to be an alternative power generation technique at present. This stems from high processing and purification costs of the Si material (single crystal costs about USD 400/kg) besides high material consumption (300 - 500 μm/wafer). This work explored the feasibility of fabricating thin film Si solar cells on low-cost polyimide (PI) substrates via thermal evaporation method in order to bring down the costs of the Si PV technology to below USD 1/Wattp. The solar cells were fabricated in substrate-configuration with p-n and p-i-n junction structures. Various light trapping strategies such as aluminium (Al) back contact reflector, PI surface texturing, zinc oxide (ZnO) anti-reflective coating (ARC) and white paint back surface reflector (BSR) have been evaluated to increase optical path length of the incident light and to reduce reflection losses. A 1.5 μm thick p-type Si absorber was used in the p-n junction cells while 800 nm intrinsic Si was adopted in the p-i-n junction cells.